Halo blight - Schwartz, Howard F. (International Center for Tropical Agriculture, 1989)
Among the bacterial diseases that attack beans are halo blight (Pseudomonas syringae pv. phaseolicola), which is distributed worldwide and survives in infected seeds and plant residue on the soil surface. Three to five days after infection, small water- soaked spots appear on the lower leaf surface, stem, and pods. Control by cultural practices is recommended as well as with chemicals and plant resistance. For successful long term control of the bacteria, integrated control programs are recommended. Symptoms and damage caused are illustrated in color. (CIAT)